THE IMPACT OF TAX CUT ON FOREIGN DIRECT INVESTMENT: A CASE STUDY IN SOUTHEAST ASIAN COUNTRIES - Nasution, Rusman Affandi (Polytechnic of State Finance STAN, 2020)
In this paper, we have examined the impact of tax cut on foreign direct investment (FDI) in Southeast Asian countries as a response to the debatable issue of the relationship between tax cut policy and FDI. We use corruption perception index and government effectiveness as the control variable, as well as other economic and demographic variables such as GDP growth, tax revenue, inflation, unemployment and population growth. Using Fixed Effect Model on panel data for a period of 1997-2016 adopted from World Bank, UNCTAD, and various websites, our findings suggest that in Southeast Asian countries, even though corporate tax cut policy gives a negative effect on FDI, this tax cut policy is not the main factor that induce investors. It is trade openness and GDP growth which become the reasons for investors to invest in this region. Moreover, the effect of government performance has played pivotal role in attracting FDI inflows.